Preparation of nutritious drink from date palm kernel - Mirghani, Mohamed Elwathig Saeed; Jaswir, Irwandi; Kabbashi, Nassereldeen A.; Mustapha, Nurul Hanan (2010)
This research work was undertaken to explore the potential use of date pits for food industry and to produce edible product which was the nutritious DPK drink. The DPK powder extracted was examined for the toxicity by using Brine Shrimp Lethality Bioassay method. After the DPK powder was confirmed to be free from any toxin, the DPK powder was analyzed for the nutritional compounds which resulted in protein 0.9809 mg, glucose 0.7351 g/L and fructose 0.6 g/L. Analysis of the mineral elements in the ash gave the following average values: Cu, 0.9227 mg/g; Ca, 2.0352 mg/g; Fe, 0.9108 mg/g; Mn, 0.4285 mg/g; Mg, 4.99 mg/g and K, 6.74 mg/g. The experiment was continued with the preparation of the DPK drink and the nutritional values of DPK drink were analyzed in which the differences in the measurement were not very significant. Factorial design was used for the optimization with 3 independent variables which were the volume of water and the amount of sucrose and citric acid. The maximum overall acceptability through the sensory evaluation test was achieved for the DPK drink formulation of 150 ml water, 300 g sucrose and 4 g citric acid with the dilution of 1:3. Analysis of the result was evaluated by using Design-Expert (DX6) software by statistical tools. Date palm kernel (DPK) contains high value-added components to be included in food products.